2009
DOI: 10.1614/wt-08-060.1
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seeding Rate Effects on Weed Management

Abstract: Studies were conducted in 2005 and 2006 at three Iowa locations to determine the effect of soybean seeding rate and glyphosate application timing on weed management and grain yields in glyphosate-resistant soybean. End-of-season weed populations were affected by soybean seeding rate at only one location, with higher weed densities present in the lowest seeding rate when glyphosate was applied at the V2 soybean growth stage. Although weed populations were not consistently affected by soybean population, weed bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 33 publications
4
50
0
1
Order By: Relevance
“…Additionally, in the MG IV region, the high seeding rate reduced pigweed biomass per square meter, biomass per plant, and seeds per square meter by 63, 57, and 67%, respectively, compared with the moderate and low seeding rates. Therefore, our results are consistent with previous findings that soybean row width and seeding rate reduced weed biomass and seed production, but not pigweed density (Arce et al 2009;Légère and Schreiber 1989). The PRE fb POST herbicide strategy was the most consistent factor to influence end-of-season pigweed density, height, biomass, and fecundity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, in the MG IV region, the high seeding rate reduced pigweed biomass per square meter, biomass per plant, and seeds per square meter by 63, 57, and 67%, respectively, compared with the moderate and low seeding rates. Therefore, our results are consistent with previous findings that soybean row width and seeding rate reduced weed biomass and seed production, but not pigweed density (Arce et al 2009;Légère and Schreiber 1989). The PRE fb POST herbicide strategy was the most consistent factor to influence end-of-season pigweed density, height, biomass, and fecundity.…”
Section: Resultssupporting
confidence: 92%
“…Edwards et al (2005) found that high seeding rates increased LI and subsequently, cumulative intercepted photosynthetically active radiation (CIPAR), more quickly; however, low seeding rates still obtained the required CIPAR to achieve 90% of the asymptotic seed yield. More-over, seeding rate had little effect on reducing weed density in a conventional production system, but reduced weed biomass (Arce et al 2009). These variable effects from seeding rate manipulation have been attributed to soybean physiological adaptations.…”
mentioning
confidence: 99%
“…These results are relevant for shade issues, leaf senescence in the lower third, and flower and pod fixation (Board and Kahlon, 2011); they are also positive for phytosanitary control (Kumudini et al, 2008) and weed management (Arce et al, 2009 …”
Section: Resultsmentioning
confidence: 88%
“…Na safra 2007 não houve diferença de rendimento de grãos, comparando-se apenas cultivares (Tabela 3 A escolha da densidade de plantas interfere no manejo integrado da soja, uma vez que densidades indicadas pela pesquisa e assistência técnica buscam conferir estabilidade produtiva para os cultivares de soja, sob condições similares de manejo e ambiente. Por exemplo, Arce et al (2009) Os resultados desta pesquisa indicam haver relação entre algumas características morfoagronômicas; a magnitude dessa relação foi explorada via análise de correlação simples, a qual se mostrou negativa entre densidade e número de ramificações por planta (r = -0,35) e densidade e número de vagens por planta (r = -0,62), bem como entre densidade e altura de plantas. Essas relações sugerem haver capacidade compensatória da densidade de plantas sobre cada caráter avaliado.…”
Section: Resultsunclassified